'Strategic' development of precision cancer medicine in the United States. Issue 7 (24th June 2021) - Schilsky, Richard L.
Abstract : The availability of advanced omics technologies has largely driven development of precision cancer medicine in the United States, but integration in routine cancer care has been challenging. Here, we consider some parameters that would enable a more coordinated, integrated, efficient, and equitable implementation of precision cancer medicine.